Contemporary Warfare and Political Jurisprudence (Fiqh Siyasah): An Analysis of Asymmetric Warfare in Military-Political Doctrine (Siyasah Harbiyyah) - Timur, Fauzia Gustarina Cempaka; Umam, Khoirul; Aulia, M. Rezza Nuril (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Islamic Jurisprudence (Fiqh) as a Legal Framework seeks to guide the dynamics of human life comprehensively, including fiqh siyasah (political jurisprudence). In warfare contexts, fiqh siyasah encompasses the practice of war (siyasah harbiyyah). However, with the evolution of warfare, questions arise about the relevance of jurisprudence to contemporary phenomena such as asymmetric warfare. By exploring Islamic sources in fiqh, particularly siyasah harbiyyah, and sources discussing new warfare forms, this paper outlines Islamic principles of warfare in analyzing asymmetric warfare. This research uses a qualitative design to examine the relationship between contemporary warfare and Fiqh Siyasah (Islamic political jurisprudence) in asymmetric warfare contexts. The data includes primary sources like classical and modern Islamic legal texts, fatwas, and religious edicts, along with secondary sources such as academic articles, books, and reports on recent asymmetric conflicts. Additionally, semi-structured interviews with Islamic legal scholars, political scientists, and defense strategists provided expert insights. Analytical methods include thematic analysis to identify key themes, content analysis to detect patterns and contradictions, and triangulation to ensure data reliability. The findings conclude that siyasah harbiyyah within fiqh cannot address the challenges of asymmetric warfare linearly, as it involves both state and non-state actors, lacks significant military involvement, and includes different war stages. This form of warfare does not always conform to international war conventions. However, the framework of fiqh principles, particularly qawaid fiqhiyyah (juridical rules), can respond to these new warfare forms. Relevant principles include views on war motivations, consequences caused by state and non-state actors, and defensive, offensive, and active defensive principles according to Islamic jurisprudence. Therefore, fiqh siyasah, especially siyasah harbiyyah, needs to accommodate responses to contemporary warfare forms in the future.